The secret horses of Briar Hill - Shepherd, Megan (Walker Books, 2016)
A girl living in a children's hospital during WWII discovers that a winged horse has entered her world and needs her help
Keywords: World War (1939-1945); Medical fiction; Sick / Juvenile fiction; Horses / Juvenile fiction; Death / Juvenile fiction; World War, 1939-1945 / Juvenile fiction; Death; Horses; Sick; 1939-1945; Fiction; Juvenile works; Children's fiction; Fiktionale Darstellung